Land Deed, Wayne County, 1877 - State of Georgia, Wayne County (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1877)
Land Deed, Wayne County, 1877. Handwritten record on ruled paper. Land grant to Willam Sapp. Wayne County, Georgia. June 1, 1877. Certified by Elias C. Fort. 3 pages.
1 electronic document [PDF/A]. Includes TIFF and JP2 images. Digitized by the Digital Library of Georgia, September 2019.
Keywords: Deeds; Wayne County (Ga.); Court records; Records and correspondence